Ruang Lingkup Filsafat terhadap Perspektif Islam pada Masa Kini - Mardinal Tarigan; Lintang Bidadari; Fauzan Alfatih (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This article discusses the scope of philosophy in the context of an Islamic perspective today. Philosophy, as a study of the nature, purpose and meaning of life, has significant relevance in understanding and deepening Islamic thought in the contemporary era. This research is a literature study that reviews the sources of Islamic philosophy and thought that are relevant today. The research results show that philosophy can broaden the understanding of Islam and provide a rational approach in dealing with contemporary issues. philosophy also contributes to solving the intellectual, social, and cultural challenges faced by Muslims today. The conclusion of this study is that philosophy in the context of Islam can help Muslims face intellectual, social and cultural challenges in a relevant and responsible way.